Health care professionals' perspectives on the requirements facilitating the roll-out of kangaroo mother care in South Africa - Wilma ten Ham; Karin C.S. Minnie; Christa S.J.C. van der Walt (AOSIS, 2016)
Background: Using best evidence to inform practice is the cornerstone of quality patient care, and requires spread, uptake, implementation and roll-out of best practices. Kangaroo mother care (KMC) was used as a best practice which has been partly rolled-out in South Africa. In order for successful roll-out of best practices, it is important to understand what health professionals perceive as requirements for the rolling-out process. However, no published research was found on requirements for rolling-out a best practice in the South African context. Purpose: of the research: To explore and describe the perspectives of health professionals on the requirements for the rolling-out process of KMC as a best practice in South Africa. Methodology: Twelve semi-structured individual interviews were conducted in 2012 with health professionals from various South African healthcare levels, involved in the implementation and the rolling-out process of kangaroo mother care. Content analysis were guided in terms of the four requirements for roll-out of best practices, identified in Edwards and Grinspun's Evidence Informed Model of Care. Results: The requirements for the successful rollout of best practices mentioned by the participants in this study concur with the requirements of Edwards and Grinspun: personal alignment and protocol/policy alignment with the best practice; a roll-out plan; leadership; and supporting and reinforcing structures such as: resources, communicating, education and development regarding the best practice, and the organisational structure. The requirements were identified at four different levels: individual level (e.g. the nurse and medical specialists), management level (of the hospital), provincial level and national level. Conclusion: Although certain requirements, such as personal alignment and reinforcing structures can be used in the roll-out of best practices, further research is desirable to promote fuller understanding of how to devise and apply the requirements in the wider adoption of best practices in South African health care settings.